Antitrust federalism in the EU and the US - Cengiz, Firat (Milton Park, Abingdon, Oxon: Routledge, 2012)
'This book analyses multi-level governance in competition policy, or'antitrust federalism' as it is called by students of competition policy, in the US and the EU from a comparative perspective. The book compares how competition laws and authorities of different levels - the federal and the state levels in the US and the national and the supranational levels in the EU - interact with each other. The EU and the US stand among the strongest existing examples of multi-level polities and they developed mature competition policies. Despite such similarities, however, recent developments imply that they are moving in different directions in the field of antitrust federalism. Inspired by these divergent policy developments taking place at both sides of the Atlantic, the book addresses three principal research questions: firstly, what are the key similarities and differences between the US and the EU in terms of antitrust federalism; secondly, what are the reasons for differences (if any), and finally, can the US and the EU draw any policy lessons from each others experiences in antitrust federalism? The book is essentially multidisciplinary in nature and it aims to initiate a dialogue between the law and political science literatures in its field. The book argues that the legal literature of antitrust federalism has employed out of date regulatory competition models which do not reflect the complexities of policy enforcement in modern multi-level polities. The book suggests that policy network models provide a more suitable framework for this analysis; and it critically reviews the British and Continental European policy network models. The book uses the common conceptual framework of European policy network models as the main analytical framework in the analysis of antitrust federalism. However, the book also shows that constitutional courts significantly affect different network designs in different polities through interpretation of constitutional power sharing and exercise mechanisms; and it critiques the political science literature for overlooking such essential role of the constitutional courts in building network models'--Provided by publisher.
'The EU and the US are the preeminent examples of multi-level polities and both have highly developed competition policies. Despite these similarities however, recent developments suggest that they are moving in different directions in the area of antitrust federalism. This book examines multi-level governance in competition policy from a comparative perspective. The book analyses how competition laws and authorities of different levels - the federal and the state levels in the US and the national and the supranational levels in the EU - interact with each other. Inspired by the increasingly divergent policy developments taking place on both sides of the Atlantic, the author asks whether the EU and the US can draw policy lessons from each other's experiences in antitrust federalism. Antitrust Federalism in the EU and the US reveals the similarities and differences between the European and American models of antitrust federalism whilst employing policy network models in its comparative analysis of issues such as opacity and accountability in networks. The book is essentially multidisciplinary in its effort to initiate dialogue between the Law and Political Science literatures in this field. This book will be of particular interest to academics, students and practitioners of Competition Law, Constitutional Law and Political Science'--Provided by publisher.
Introduction -- Searching for a model of multi-level policy enforcement : models of regulatory competition and policy networks -- Relations between competition laws and federalism in the US and the EU -- Relations between competition authorities : networks in the US and the EU -- Conclusions. Antitrust federalism in the US and the EU, transatlantic policy learning and contributions to the theory.
Includes bibliographical references (p. [200]-222) and index.
Keywords: Antitrust law -- United States; Antitrust law -- European Union countries; Federal government -- United States; Federal government -- European Union countries